Ceza Muhakemesi Hukukunda Elkoyma ve Şirket Yönetimi için Kayyum atama tedbirleri - Tok, Mehmet Can (Seçkin Yayıncılık, 2018)
Ceza Muhakemesi Hukukunda soruşturma ve kovuşturmanın etkili bir biçimde yürütülebilmesi ve kovuşturmanın sonucunda verilecek hükümden beklenen faydaların elde edilebilmesi birtakım önlemler öngörülmüştür. Bu önlemlere koruma tedbirleri adı verilmektedir. Gerek Ceza Muhakemesi Kanununda gerekse başka kanunlarda çok sayıda koruma tedbirleri düzenlenmiştir. Bu çalışmada, 5271 sayılı Ceza Muhakemesi Kanununda öngörülmüş olan elkoyma ve şirket yönetimi için kayyım atama tedbirleri incelenecektir.

There are measures taken in crimal procedure law to ensure the efficiency of investigation and prosecution, and to protect the legal interest in the verdict given at the end of the prosecution. Those measures are named as protection measures. Protection measures are anacted not only in the Code of Criminal Procedure but also in several other codes. In this study, two of those protection measures enacted in the Code of Criminal Prrocedure no. 5271, namely seizure and appointment of trustee for the administration of a company, will be analysed.
Measure of Seizure and Appointment of a Trustee for the Administration of a Company in Criminal Procedure law
Keywords: Ceza Muhakeme Hukuku; Koruma Tedbirleri; Elkoyma; Şirket Yönetimi İçin Kayyım Atama; Criminal Procedure Law; Protection Measures; Seizure; Appointment of a Trustee for the Administration of a Company